2017
DOI: 10.1111/mmi.13619
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxybenzoic acid is a diffusible factor that connects metabolic shikimate pathway to the biosynthesis of a unique antifungal metabolite in Lysobacter enzymogenes

Abstract: Heat-stable antifungal factor (HSAF) produced by Lysobacter enzymogenes is a potential lead compound for developing new antibiotics. Yet, how L. enzymogenes regulates the HSAF biosynthesis remains largely unknown. Here, we show that 4-hydroxybenzoic acid (4-HBA) serves as a diffusible factor for regulating HSAF biosynthesis. The biosynthesis of 4-HBA involved an oxygenase, LenB2, and mutation of lenB2 almost completely abolished 4-HBA production, leading to significantly impaired HSAF production. Introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…Binding of the Clp-GST fusion protein to the HSAF operon promoter ( 39 ) was determined by MST using Monolith NT.115 (NanoTemper Technologies, Germany), according to the recently described protocol ( 16 ). Briefly, the 50-bp DNA fragments were labeled with 5-carboxy-fluorescein (FAM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of the Clp-GST fusion protein to the HSAF operon promoter ( 39 ) was determined by MST using Monolith NT.115 (NanoTemper Technologies, Germany), according to the recently described protocol ( 16 ). Briefly, the 50-bp DNA fragments were labeled with 5-carboxy-fluorescein (FAM).…”
Section: Methodsmentioning
confidence: 99%
“…Lysobacter enzymogenes is a nonpathogenic, plant-associated gammaproteobacterium known for synthesis of the antifungal antibiotic Heat-Stable Antifungal Factor, HSAF ( 11–14 ), which makes it an attractive biological control agent for fungal diseases of agriculturally important plants ( 11 , 12 , 15 ). Therefore, identifying genes and growth conditions that regulate HSAF production has been of significant interest ( 16 , 17 ). Our earlier work revealed that elevated intracellular c-di-GMP levels are detrimental for HSAF production due to lower HSAF biosynthesis gene expression ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…; Su et al . ). The two signalling molecules have a distinct role in the physiology of L. enzymogenes OH11, with 3‐HBA involved in the biosynthesis of the xanthomonadin‐like pigment (Qian et al .…”
Section: The Regulatory Network In Lysobacter Enzymogenesmentioning
confidence: 97%
“…) and 4‐HBA directly involved in HSAF biosynthesis through the activity of the regulatory protein LysR Le , belonging to the LysR family (Su et al . ).…”
Section: The Regulatory Network In Lysobacter Enzymogenesmentioning
confidence: 97%
See 1 more Smart Citation